The wily planthopper: A new genus and species of Flatidae (Hemiptera: Fulgoromorpha: Fulgoroidea) from Florida with implications for the American Selizini - Hendrix, Solomon V.; Wilson, Stephen W.; Halbert, Susan E.; Bartlett, Charles R. (Zootaxa, 2026)
The flatid genus Vafer gen. nov. is described to accommodate two species: a new species from Florida, Vafer contractus sp. nov., and the Mexican species, Vafer plebeius (Kirkaldy) comb. nov., the latter transferred from Ormenis Stål. Vafer contractus sp. nov. is likely adventive to Florida from Central America. Vafer gen. nov. is placed in Flatinae, tribe Selizini. An amended diagnosis of Selizini is provided in the context of American taxa with representative genera illustrated and a list of included taxa. A key to the selizine genera north of Mexico is provided, and the historic composition of the tribe is reviewed. Two tribes are described from genera segregated from Selizini: Dascalini tribe nov. (accommodating Dascalia Stål, Leptodascalia Melichar, Locrona Fennah, and Pseudodascalia Melichar) and Exomini tribe nov. (accommodating Deocerus Metcalf & Bruner, Exoma Melichar, and Samcerus Medler). The genera Acanthoflata Fieber, Arelate Stål, Byllisana Metcalf & Bruner, and Ormenina Fennah are transferred to Selizini from other tribes. The genera Capistra Fennah and Eurocalia Van Duzee are transferred from Phromniini and Selizini, respectively, to Flatoidini (Flatoidinae).